Calculation of vibrational energy of molecule using coupled cluster linear response theory in bosonic representation: convergence studies - Banik, Subrata; Pal, Sourav; Prasad, M. Durga (Journal of Chemical Physics, 2008)
Vibrational excited state energies have been calculated using vibrational coupled cluster linear response theory (CCLRT). The method has been implemented on formaldehyde and water molecule. Convergence studies have been shown with varying the cluster operator from S(4) to S(6) as well as the excitation operator from four bosons to six bosons. A good agreement with full configuration interaction results has been observed with S(6) truncation at coupled-cluster method level and six bosonic excitations at CCLRT level. (C) 2008 American Institute of Physics.